DeCarlo Ch16b Solutions

Linear Circuit Analysis: The Time Domain and Phasor Approach

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
1/25/02 P16-1 © R. A. DeCarlo, P. M. Lin SOLUTION 16.31. In order to compute the area beneath v ( t - ) h ( ) seven regions will be considered: t < 0, 0 t < 1, 1 t < 2, 2 t < 3, 3 t < 4, 4 t < 5 and 5 t . Step 1: t < 0. For t in this region v ( t - ) h ( ) = 0 for all . Hence y ( t ) = v ( t ) h ( t ) = 0 for t < 0. Step 2: 0 t < 1. In this case v ( t - ) h ( ) = v 0 × h 0 for 0 t and is zero otherwise. Therefore the area beneath v ( t - ) h ( ) equals y ( t ) = v ( t ) h ( t ) = v 0 × h 0 × t for 0 t < 1. Step 3: 1 t < 2. For t in this region we have v ( t - ) h ( ) = v 1 × h 0, 0 t - 1 v 0 × h 0, t - 1 < < 1 v 0 × h 1, 1 < t 0, otherwise Therefore the area beneath v ( t - ) h ( ) equals y ( t ) = v ( t ) h ( t ) = v 1 × h 0 × ( t - 1) - 0 [ ] + v 0 × h 0 × 1 - ( t - 1) [ ] + v 0 × h 1 × ( t - 1) = = t × ( v 1 × h 0 - v 0 × h 0 + v 0 × h 1) - v 1 × h 0 + 2 × v 0 × h 0 - v 0 × h 1, for 1 t < 2 Step 4: 2 t < 3. In this case v ( t - ) h ( ) = v 1 × h 0, t - 2 < < 1 v 1 × h 1, 1 t - 1 v 0 × h 1, t - 1 < < 2 v 0 × h 2, 2 < t 0, otherwise Hence, for 2 t < 3, y ( t ) = v ( t ) h ( t ) = = v 1 × h 0 × 1 - ( t - 2) [ ] + v 1 × h 1 × ( t - 1) - 1 [ ] + v 0 × h 1 × 2 - ( t - 1) [ ] + v 0 × h 2 × ( t - 2) = = t × ( - v 1 × h 0 + v 1 × h 1 - v 0 × h 1 + v 0 × h 2) + 3 × v 1 × h 0 - 2 × v 1 × h 1 + 3 × v 0 × h 1 - 2 × v 0 × h 2 Step 5: 3 t < 4. In this case v ( t - ) h ( ) = v 1 × h 1, t - 2 < < 2 v 1 × h 2, 2 t - 1 v 0 × h 2, t - 1 < < 3 0, otherwise Hence, for 3 t < 4, y ( t ) = v ( t ) h ( t ) = = v 1 × h 1 × 2 - ( t - 2) [ ] + v 1 × h 2 × ( t - 1) - 2 [ ] + v 0 × h 2 × 3 - ( t - 1) [ ] = = t × ( - v 1 × h 1 + v 1 × h 2 - v 0 × h 2) + 4 × v 1 × h 1 - 3 × v 1 × h 2 + 4 × v 0 × h 2 Step 6: 4 t < 5. In this case v ( t - ) h ( ) = v 1 × h 2 for t - 2 < < 3 and is zero otherwise. Therefore y ( t ) = v ( t ) h ( t ) = v 1 × h 2 × 3 - ( t - 2) [ ] = v 1 × h 2 × (5 - t ) for 4 t < 5.
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
1/25/02 P16-2 © R. A. DeCarlo, P. M. Lin Step 7: 5 t . For t in this region v ( t - ) h ( ) = 0 for all . Hence y ( t ) = v ( t ) h ( t ) = 0 for 5 t . In sum, y ( t ) = v 0 × h 0 × t , 0 t < 1 t × ( v 1 × h 0 - v 0 × h 0 + v 0 × h 1) - v 1 × h 0 + 2 × v 0 × h 0 - v 0 × h 1, 1 t < 2 t × ( - v 1 × h 0 + v 1 × h 1 - v 0 × h 1 + v 0 × h 2) + 3 × v 1 × h 0 - 2 × v 1 × h 1 + 3 × v 0 × h 1 - 2 × v 0 × h 2, 2 t < 3 t × ( - v 1 × h 1 + v 1 × h 2 - v 0 × h 2) + 4 × v 1 × h 1 - 3 × v 1 × h 2 + 4 × v 0 × h 2, 3 t < 4 v 1 × h 2 × (5 - t ), 4 t < 5 0, otherwise Hence, y 1 = y (1) = v 0 × h 0 = 6 y 2 = y (2) = v 0 × h 1 + v 1 × h 0 = 8 y 3 = y (3) = v 0 × h 2 + v 1 × h 1 = - 6 y 4 = y (4) = v 1 × h 2 = 4 (b) Using the expressions of p ( x ) and q ( x ) it follows that p ( x ) × q ( x ) = x 3 × ( v 0 × h 0) + x 2 × ( v 0 × h 1 + v 1 × h 0) + x × ( v 0 × h 0 + v 1 × h 1) + v 1 × h 2 We observe that the coefficients of p ( x ) × q ( x ) are exactly y 1 , y 2
Background image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

This document was uploaded on 01/24/2008.

Page1 / 39

DeCarlo Ch16b Solutions - 1/25/02 P16-1 R. A. DeCarlo, P....

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online